Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/toxins11040183
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Zhen, Z. et al. NaCl Inhibits Citrinin and Stimulates Monascus Pigments and Monacolin K Production. Toxins 2019, 11, 118

Abstract: The authors wish to make the following correction to their paper [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…16 It has also been reported that preparation process parameters can influence the final capsule size and size distribution; the main factors are polymerization conditions such as polymer reaction temperature, chemical structure of shell materials, structure of the reactor, agitation speed, and pH. 17 In this experiment, however, the preparation conditions were the same and only the shell and core materials were varied; thus, size variations were mainly driven by the different combinations of monomers, liquid hydrocarbons, and catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…16 It has also been reported that preparation process parameters can influence the final capsule size and size distribution; the main factors are polymerization conditions such as polymer reaction temperature, chemical structure of shell materials, structure of the reactor, agitation speed, and pH. 17 In this experiment, however, the preparation conditions were the same and only the shell and core materials were varied; thus, size variations were mainly driven by the different combinations of monomers, liquid hydrocarbons, and catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…ATPAF1 was identified as a key candidate gene through machine learning approaches. As a mitochondria-localized protein, ATPAF1 is essential for ATP synthase assembly and mitochondrial oxidative phosphorylation (Zhou et al, 2021). Although abnormal ATPAF1expression has been reported in asthma and kidney cancer (Schauberger et al, 2011;Bruggemann et al, 2017), its involvement in human diseases remains unclear.…”
Section: Discussionmentioning
confidence: 99%